"Synne and Sedition": Peter Martyr Vermigli's "Sermon concernynge the tyme of rebellion" in the Parker Library. - Kirby, Torrance (Sixteenth Century Journal)
An autograph sermon by Peter Martyr Vermigli with Matthew Parker's annotation "Sermo Petri Martir manu propria scripta in seditionem Devonensium" is included among the Reformation manuscripts in the Parker Library of Corpus Christi College, Cambridge. Preached at St. Paul's (although not by Vermigli himself), the sermon constitutes a response to the popular uprising in Devon and other parts of the realm precipitated by the promulgation of the first Edwardine Act of Uniformity of 1549 with its prescription of the new vernacular liturgy of the Book of Common Prayer. Vermigli offers a measured response to the actions of both the rebels and the governing authorities based upon an appeal to the principles of an Augustinian political theology. All parties to the conflict—government, gentry, and commons—are found to be at fault and Vermigli proposes penance all round as the "remedie of al our plags."